Recent social trends in France, 1960-1990 - Forsé, Michel (Comparative charting of social change in contemporary society., 1993)
A prominent feature of the social revolution in France has been the decline of the great national institutions -- the Republic, the Army, the church, and the schools -- which are losing their symbolic value and are no longer the targets of ideological disputes. As a result, there is a growing basic consensus among the French people. At the same time, the French have developed a new interest in managing local problems -- due to the decentralization law -- which has led to the establishment of many voluntary associations. Changes in family life following the "revolution" of 1968 have led to greater instability among couples, but at the same time have strengthened the kinship system resulting in increased life expectancy. The customs of the French have also changed. The French education system, originally based on authority and regulations, is now making increasing use of experimentation and negotiation. As a result, the attitude of the French towards authority has totally changed and the French have learned to negotiate and cooperate among themselves. All these changes can be interpreted as progressive moves toward liberty, equality, and individualism. There is little danger of social instability, since French society remains in remarkably robust health